Genotoxic Effect of Dicyclopropanated 5-Vinyl-2-Norbornene - Uliana S. Novoyatlova; Andrei G. Kessenikh; Olga V. Kononchuk; Sergey V. Bazhenov; Alexander A. Fomkin; Anna A. Kudryavtseva; Sergey V. Shorunov; Maxim V. Bermeshev; Ilya V. Manukhov (Biosensors, 2022)
Dicyclopropanated 5-vinyl-2-norbornene (dcpVNB) is a strained polycyclic hydrocarbon compound with a high energy content, which makes it promising for the development of propellant components based on it. In this work, the genotoxic properties of dcpVNB were studied using whole-cell lux-biosensors based on Escherichia coli and Bacillus subtilis. It was shown that the addition of dcpVNB to bacterial cells leads to the appearance of DNA damage inducing the SOS response and Dps expression with slight activation of the OxyR-mediated response to oxidative stress. The highest toxic effect of dcpVNB is detected by the following lux-biosensors: E. coli pColD-lux, E. coli pDps, B. subtilis pNK-DinC, and B. subtilis pNK-MrgA, in which the genes of bacterial luciferases are transcriptionally fused to the corresponding promoters: Pcda, Pdps, PdinC, and PmrgA. It was shown that lux-biosensors based on B. subtilis, and E. coli are almost equally sensitive to dcpVNB, which indicates the same permeability to this compound of cell wall of Gram-positive and Gram-negative bacteria. The activation of Pdps after dcpVNB addition maintains even in oxyR mutant E. coli strains, which means that the Pdps induction is only partially determined by the OxyR/S regulon. Comparison of specific stress effects caused by dcpVNB and 2-ethyl(bicyclo[2.2.1]heptane) (EBH), characterized by the absence of cyclopropanated groups, shows that structural changes in hydrocarbons could significantly change the mode of toxicity.